2008
DOI: 10.1021/jo7023224
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Effects of Halogen Substitution and Solvent on the Rates and Mechanisms of Nucleophilic Substitution Reactions of Aziridines

Abstract: In a previous study we reported that fluorine substitution at the carbon positions of aziridine results in profound enhancements of the rate of reaction with ammonia, a typical nucleophile, in the gas phase. In this study the investigation is extended to include chloro- and bromoaziridines. Because syntheses are largely performed in the condensed phase, the present computational investigation [(MP2(Full)/6-311++G(d,p)//MP2(Full)/6-31+G(d) level] was conducted with three typical solvents that cover a wide range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…To our delight, reaction was completed within 5 min to afford chloroamine 2a as the only product in 99% yield (Scheme ). The high regioslectivity is in accordance with the experimental , as well as extensive computational studies …”
Section: Resultssupporting
confidence: 87%
“…To our delight, reaction was completed within 5 min to afford chloroamine 2a as the only product in 99% yield (Scheme ). The high regioslectivity is in accordance with the experimental , as well as extensive computational studies …”
Section: Resultssupporting
confidence: 87%
“…Another study that showed rate acceleration with increasing ligand size was for nucleophilic substitutions at aziridine (see Scheme ). Banks used MP2 calculations to show that the activation barrier Δ H ≠ decreased from 63.4 kcal mol −1 for X=Y=H to 33.0 kcal mol −1 for X=Y=Cl, and to 31.5 kcal mol −1 for X=Y=Br.…”
Section: Bulkiness Of Substituentsmentioning
confidence: 99%
“…Substitution of the carbon positions of the aziridine ring with fluorine, chlorine, or bromine also led to spectacularly elevated rates of ring cleavage reactions. 21,22 But also with such substitutions new reaction possibilities are opened that might decrease the inhibition potency. 22 Our first attempt advises that for an improvement of the potency on the basis of k i substituents should be used that do not open up new reaction paths.…”
Section: Introductionmentioning
confidence: 99%